Exploratory Descriptive Analysis About Business Models in New Media: Strategies and Challenges - Flores-Vivar, Jesús Miguel (2021)
Digitization has brought with it an increase in the supply of media and content, which has led to an increase in competition for news companies both in terms of audience and income. But how to convert that audience that is migrating from paper to the digital environment into income? In this paper, an exploratory and descriptive analysis of the business models of journalistic companies in the digital environmentis made. For this reason, three objectives are proposed: to know the main marketing strategies, identify the conditions that have influenced decision-making and detect market challenges. Based on which, the reports made by the Reuters Institute, Pew Research Center, Poynter Institute, Evoca and the Association of Information Media are taken as a reference, as well as the contributions of various researchers on thesubject. It is found that, among the strategies developed, charging for content prevails in its various modalities, conditioned by the transformation in the value chain. It is necessary to face new challenges and adding value to a client who has lost confidence, personalizing services and constant adaptation to the impact of digital transformation.